Aromatic Hydrocarbons of Wondama Coal, Papua Barat - Christoffel S I Maweikere; R Y Perry Burhan (IPTEK Journal of Proceedings Series, 2015)
Wondama coal were subjected to solvent extraction and aromatic hydrocarbon fractions obtained by thin layer chromatography with n-hexane as eluent. Aromatic fractions identified by Gas Chromatography-Mass Spectroscopy (GC-MS). Aromatic seskuiterpenoids, diterpenoid and triterpenoids were found in Wondama coal. This composition illustrates sources of organic matter derived from terrestrial higher plants.